Do public budget deficits crowd out private capital expenditures? The case of the United States, 1981–1984 - Hans-Peter Fröhlich (Intereconomics, 1985)
Those economists who expected the increasing US budget deficits in recent years to have a negative impact on private investment spending have so far been proved wrong. Hans-Peter Fröhlich provides an analysis of what has happened and examines the interrelation between public sector deficits and private capital expenditures.
Keywords: 330; Budgetary Policy